2019
DOI: 10.1088/1757-899x/579/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery of Heavy Oil Using A Catalytic Process

Abstract: Oil is a major source of energy around the world. With the decline of light conventional oil, more attention is being paid to heavy oil and bitumen, as a good alternative to light oil for energy supplies. Heavy crude oils have a tendency to have a higher concentration of metals and several other elements such as sulfur and nitrogen, and extraction of these heavy oils requires more effort and cost. Toe-to-Heel Air Injection (THAI) is a novel process of enhanced heavy oil and bitumen recovery and upgrading. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…8 where the hydrogen sulphide formed due to carbon-sulphur bond breakage and carbon-hydrogen and sulphur-hydrogen bonds formations is generally larger in model P56 than in model P45. This new key finding was not shown by the previous study by Hasan and Rigby (2019).…”
Section: Degree Of Upgrading (Api Gravity)contrasting
confidence: 88%
See 2 more Smart Citations
“…8 where the hydrogen sulphide formed due to carbon-sulphur bond breakage and carbon-hydrogen and sulphur-hydrogen bonds formations is generally larger in model P56 than in model P45. This new key finding was not shown by the previous study by Hasan and Rigby (2019).…”
Section: Degree Of Upgrading (Api Gravity)contrasting
confidence: 88%
“…The first simulation study of the THAI-CAPRI process was conducted by Rabiu Ado ( 2017 ) where a catalyst packing porosity of 45%, which lies in between the 44% and 45.1% reported from experimental studies performed by Abu et al ( 2015 ), was used. Then, using the Rabiu Ado’s ( 2017 ) THAI-CAPRI numerical model, Hasan and Rigby ( 2019 ) conducted a numerical simulation studies where they reported the effect of the catalyst packing porosity on the cumulative oil production and the peak temperature. However, their study has three limitations: (1) They only investigated packing porosities of 44%, 44.55%, and 45.1%, and that means the differences in the packing porosities are so small that no pronounced effect was observed both with the cumulative oil production and the peak temperature, (2) they only considered two parameters (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the catalyst component details can be found in Hasan and Rigby, 23 where a 44% packing porosity is employed. To represent the catalytic upgrading of the HO, a new hydrogenation reaction was introduced into the model (Reaction 8; Table 5 ).…”
Section: Model Developmentmentioning
confidence: 99%
“…THAI–CAPRI did not undergo numerical modeling until Hasan and Rigby 23 used CMG STARS, a thermal processes reservoir simulation software, to model laboratory-scale THAI–CAPRI utilizing the co-injection of air/oxygen and hydrogen. The injected hydrogen was used to represent the potential hydrogen produced through reactions such as water gas shift and coke gasification.…”
Section: Introductionmentioning
confidence: 99%